KontraS dan Dinamika Kebijakan Negara dalam Penyelesaian Pelanggaran HAM Berat di Indonesia - Ahmad Zuhdi Azizi (CV Global Research Publication, 2026)
Indonesia has a legacy of gross human rights violations that have not yet been resolved through the judicial system, including the forced disappearances of activists in 1997–1998—13 of whom remain missing to this day—the Tanjung Priok and Semanggi tragedies, and the protracted conflicts in Papua and Aceh. Although Law No. 26 of 2000 on Human Rights Courts and Presidential Regulation No. 17 of 2022 on the Non-Judicial Resolution of Past Serious Human Rights Violations are available as instruments of state legal protection, their implementation is considered far from adequate because it depends on the absent political will of the executive branch. This gap forms the backdrop for this study on the role of the Commission for the Missing and Victims of Violence (KontraS) as a human rights advocacy group in influencing central government policy regarding the handling of gross human rights violations in Indonesia. Using a qualitative single-case study approach with document analysis techniques, this research examines secondary data from 2019 to 2025, employing a theoretical framework that integrates advocacy group theory and role theory. The findings indicate that KontraS performs five mutually reinforcing roles: documenter of human rights violations, victim advocate, policy advocate, international liaison, and public watchdog. The role of independent documenter and international opinion-shaper has proven most effective in creating reputational pressure on the government, as reflected in KontraS’s involvement in the UN Universal Periodic Review mechanism and the FIDH network. Direct policy advocacy is hampered by the executive branch’s lack of political will and the absence of independent judicial mechanisms. This study concludes that KontraS’s effectiveness lies in its capacity to build international reputational pressure and provide a credible independent database, while affirming that the formal legal framework cannot function optimally without sustained civil society advocacy pressure.